2021
DOI: 10.1111/jch.14362
|View full text |Cite
|
Sign up to set email alerts
|

The effects of different antihypertensive drugs on pain and joint space width of knee osteoarthritis – A comparative study with data from Osteoarthritis Initiative

Abstract: Hypertension was one common comorbidity of knee osteoarthritis (KOA), but the effect of different types of antihypertensive drugs on pain and joint space width (JSW) was unclear and not compared. Four hundred ninety KOA patients using one of the beta-blockers, ACE inhibitors, angiotensin receptor blockers, Calcium channel blockers (CCBs), or thiazide diuretics were followed for four years. The blood pressure, cumulative knee replacement rate, Womac pain, and JSW were compared among groups.All data were from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…9,18 A systematic review did not find associations between calcium channel blocker use and migraine outcomes. 18 However, a multicenter cohort study of people with knee osteoarthritis found associations between calcium channel blocker use and worse pain outcomes, 52 consistent with the current study. In contrast, an unpublished agnostic drug repurposing MR study of pain intensity irrespective of pain location suggested potential analgesic effects of calcium channel blockers.…”
Section: Discussionsupporting
confidence: 88%
“…9,18 A systematic review did not find associations between calcium channel blocker use and migraine outcomes. 18 However, a multicenter cohort study of people with knee osteoarthritis found associations between calcium channel blocker use and worse pain outcomes, 52 consistent with the current study. In contrast, an unpublished agnostic drug repurposing MR study of pain intensity irrespective of pain location suggested potential analgesic effects of calcium channel blockers.…”
Section: Discussionsupporting
confidence: 88%
“…By analyzing the effects of different classes of antihypertensive drugs on pain and joint space width among 1945 patients who used antihypertensive drugs from the Osteoarthritis Initiative project, it has been shown that, among females, the users of calcium channel blockers exhibited significantly higher pain scores than the groups using beta-blockers and angiotensin receptor blockers. Compared to the common antihypertensive drugs (beta-blockers, ACE inhibitors, angiotensin receptor blockers, and thiazide diuretics), calcium channel blockers were associated with reduced joint space width, higher replacement rates, and higher pain scores [ 34 ]. An antinociceptive effect has been demonstrated for the beta blocker bupranolol in a mouse model of chronic pain [ 35 ].…”
Section: Therapeutic Considerations In Metabolic Knee Osteoarthritismentioning
confidence: 99%
“…Beta-blockers have been shown to be associated with lower WOMAC scores and statistically significantly lower risk of joint pain, whereas other authors detected no evidence of analgesic effect. 131,132 Calcium channel blockers, on the other hand, have been associated with higher pain scores and a higher prevalence of joint replacement. [132][133][134] What is more concerning is the idea that calcium channel blockers may accelerate the process of OA by impairing the proliferation of chondrocytes.…”
Section: Antihypertensivesmentioning
confidence: 99%
“…131,132 Calcium channel blockers, on the other hand, have been associated with higher pain scores and a higher prevalence of joint replacement. [132][133][134] What is more concerning is the idea that calcium channel blockers may accelerate the process of OA by impairing the proliferation of chondrocytes. 135 The evidence is extremely limited on the use of these classes of medication for knee pain, and recommendations cannot be made for or against their use.…”
Section: Antihypertensivesmentioning
confidence: 99%